1992
DOI: 10.1002/bit.260401114
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of biphenyl and PCBs by the white rot fungus Phanerochaete chrysosporium

Abstract: The white rot fungus Phanerochaete chrysosporium is unique in its ability to totally degrade a wide variety of recalcitrant pollutants. We have investigated the degradation of biphenyl and two model chlorinated biphenyls, 2,2',4,4'-tetrachlorobiphenyl and 2-chlorobiphenyl by suspended cultures of P. chrysosporium grown under conditions that maximize the synthesis of lignin-oxidizing enzymes. Radiolabeled biphenyl and 2'-chlorobiphenyl added to cultures at concentrations in the range 260 nM to 8.8 microM were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
3
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 39 publications
(1 reference statement)
3
32
3
1
Order By: Relevance
“…Also the Pseudomonas spp showed highest turbidity (0.727-0.371) and lowest pH values (3.55-3.68). Biodegradation rates are highly variable because they depend on several factors, including the amount and location of chlorination, PCB concentration, type of microbial population, available nutrients, and temperature (Thomas et al, 1992;Robinson and Lenn, 1994). Pseudomonas spp, Arthrobacter spp, and Micrococcus spp utilized the askarel oil ( a PCB blend) appreciably at different concentrations in 15µL and 20µL but minimally at 5µL and 10µL.…”
Section: Discussionmentioning
confidence: 99%
“…Also the Pseudomonas spp showed highest turbidity (0.727-0.371) and lowest pH values (3.55-3.68). Biodegradation rates are highly variable because they depend on several factors, including the amount and location of chlorination, PCB concentration, type of microbial population, available nutrients, and temperature (Thomas et al, 1992;Robinson and Lenn, 1994). Pseudomonas spp, Arthrobacter spp, and Micrococcus spp utilized the askarel oil ( a PCB blend) appreciably at different concentrations in 15µL and 20µL but minimally at 5µL and 10µL.…”
Section: Discussionmentioning
confidence: 99%
“…Zeddel et al (1993) described a degradation rate of 95% for chlorinated biphenyls containing up to four chlorine ions by the white rot fungus Trametes versicolor. However, the mineralisation rate achieved by several white rot fungi was not above 10% (Thomas et al 1992;Dietrich et al 1995;Vyas et al 1994;Beaudette et al 1998). This difference could be explained by the formation of products that are not easy to analyse.…”
Section: Introductionmentioning
confidence: 95%
“…Some fungi, such as Phanerochaete chrysosporium and Aspergillus fumigatus are known for their ability to degrade some recalcitrant pollutants such as synthetic polymers. The former is called white rot fungus and degrades lignin and synthetic polymers (Martins et al, 2001;Thomas et al, 1992;Lymar et al, 1995) and the latter has been described as an effective degrader of plasticized PVC and DDT. Scanning Electronic Microscopy (SEM) studies with this fungus on poly-hydroxybutirate-co-valerate samples showed degradation on their surfaces (Renstad et al, 1999).…”
Section: Introductionmentioning
confidence: 99%